2023
DOI: 10.1186/s10020-023-00716-4
|View full text |Cite
|
Sign up to set email alerts
|

Oral probiotics increased the proportion of Treg, Tfr, and Breg cells to inhibit the inflammatory response and impede gestational diabetes mellitus

Weijie Liang,
Yuanyi Feng,
Dongmei Yang
et al.

Abstract: Background Children of mothers with gestational diabetes mellitus (GDM) are more prone to acquire type 2 diabetes and obesity as adults. Due to this link, early intervention strategies that alter the gut microbiome may benefit the mother and kid long-term. This work uses metagenomic and transcriptome sequencing to investigate how probiotics affect gut microbiota dysbiosis and inflammation in GDM. Methods GDM and control metagenomic sequencing data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 82 publications
(122 reference statements)
0
7
0
Order By: Relevance
“…Disturbed gut microbiota produces large amounts of LPS, which leads to a variety of different biological activities. For example, Liang et al (2023) found that oral administration of probiotics significantly reduced Gram-negative bacterial counts, lowered inflammatory factor levels, and prevented GDM. Prebiotics such as isomaltodextrin have beneficial effects on chronic inflammation-associated insulin resistance by restoring the intestinal barrier and reducing circulating endotoxin levels (Hann et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Disturbed gut microbiota produces large amounts of LPS, which leads to a variety of different biological activities. For example, Liang et al (2023) found that oral administration of probiotics significantly reduced Gram-negative bacterial counts, lowered inflammatory factor levels, and prevented GDM. Prebiotics such as isomaltodextrin have beneficial effects on chronic inflammation-associated insulin resistance by restoring the intestinal barrier and reducing circulating endotoxin levels (Hann et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…After the intervention, hypersensitive C-reactive protein (hs-CRP), TNF-α, and IL-6 levels were significantly reduced in women with GDM who were treated with probiotics compared to the placebo group ( 235 ). A recent study proved that oral probiotics increased Tregs, Tfrs and Bregs and decreased proinflammatory cytokines to prevent inflammation in mice with GDM ( 47 ), which showed the effect of probiotics on regulating the immune response. Additionally, probiotics can reverse the phenotype of GDM through the metabolism pathways of amino acids, bile acids, porphyrin, and chlorophyll ( 236 ).…”
Section: Potential Therapeutic Strategiesmentioning
confidence: 99%
“…When fed with a diet enriched in prebiotics, the abundance of Tregs increased in the placenta, and Bregs increased in both the placenta and the uterus, followed by the alteration of gut microbiota ( 46 ). It has been proved recently that oral probiotics also increased Tregs, Bregs and follicular regulatory T cells (Tfr), as well as IL-10 and transforming growth factor-β (TGF-β), while decreased TNF-α and IL-6 to prevent inflammation in mice with GDM ( Figure 1 ) ( 47 ). In a sow model, a higher abundance of Bacteroides fragilis was associated with higher levels of LPS, IL-1β and IL-6 as well as increased intestinal permeability ( 48 ).…”
Section: Maternal Gut Microbiota and The Immune Response During Pregn...mentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnancy is a unique biological process in which orchestrated hormonal, metabolic and immunological changes promote fetal nourishment and development within the maternal womb. These physiological adaptations interact dynamically with the microbiota resident in the gut, so that maternal hormonal and metabolic changes shape the structure and diversity of the bacterial community, 49,50 and conversely, microbial byproducts modulate pregnancy‐associated processes including placental development 51,52 and feto‐maternal tolerance 53–56 . Indeed, the bidirectional nature of these interactions is evidenced by the increasing amount of research demonstrating the direct link between imbalances of the microbiota and adverse pregnancy outcomes such as preeclampsia, fetal growth restriction, preterm birth, and gestational diabetes (reviewed in 57 ).…”
Section: Intrinsic Influences: Pregnancy‐specific Remodeling Of the G...mentioning
confidence: 99%